Changes in Rosuvastatin Pharmacokinetics During Postnatal Ontogenesis in Rats - Jaroslava Roušarová; Martin Šíma; Petr Kozlík; Tomáš Křížek; Ondřej Slanař (Frontiers Media S.A., 2021)
Purpose: Statin therapy should be considered in children with familial hypercholesterolemia and sustained high LDL-C levels. There are no data on rosuvastatin exposure in patients <6 years and efficacy/safety can only be derived from case reports. Our aim was to examine developmental changes in pharmacokinetics of rosuvastatin in rats in vivo as a basis for clinical development of formulations for patients < 6 years. Methods: Rosuvastatin pharmacokinetics was examined in rats aged 1, 4, 7, 10, 14, 21, 28, 35 and 42 days (from birth to sexual maturity). After intraperitoneal dose of 5 mg/kg, blood samples to determine serum rosuvastatin levels were taken at 0.5, 3 and 5 hours. Pharmacokinetic parameters (Vd, CL, AUClast, AUC0-∞) were calculated using pharmacokinecic simulations. Results: Both rosuvastatin CL and Vd started to increase systematically between 2 - 3 weeks of age, which was reflected by decreased total drug exposure. The AUC was up to 13 times higher in the age groups ≤14 days compared with the value at 42 days. Conclusions: Based on interspecies scaling, a dose reduction could be a feasible way, how to develop appropriate dosing schedule and formulations for children aged 2 - 6 years. However, confirmation in clinical development studies will be needed.